1996
DOI: 10.1093/jn/126.5.1438
|View full text |Cite
|
Sign up to set email alerts
|

Methionine and 2-Hydroxy-4-Methylthiobutanoic Acid Are Partially Converted to Nonabsorbed Compounds during Passage through the Small Intestine and Heat Exposure Does Not Affect Small Intestinal Absorption of Methionine Sources in Broiler Chicks

Abstract: Broiler chicks were fed diets supplemented with DL-methionine or DL-2-hydroxy-4-methyl-thiobutanoic acid. At 4 wk of age the chicks were subdivided into thermoneutral (22 degrees C) and heat-exposed (32 degrees C) groups and maintained under these conditions for 48 h. Highly purified 3H-L-methionine (3H-L-Met) and 3H-L-2-hydroxy-4-methyl-thiobutanoic acid (3H-L-HMB) were used to evaluate treatment effects on the small intestinal passage of sources of supplemental methionine and on the transport of methionine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…The oligomers of liquid MHA-FA are poorly absorbed (Saunderson, 1991) and of a lower bioavailability in poultry compared to the commercial product mix of mono-, di-and oligomers (Van Weerden et al, 1992). Maenz and Engele-Schaan (1996b) also reported that in broilers there was conversion of L-MHA into non-absorbable by-products during its passage through the gastro-intestinal tract. Additionally, Malik et al (2006) showed that liquid MHA was, in fact, more slowly absorbed throughout the digestive tract of pigs than L-Met, which agrees with Drew et al (2003) who observed similar results in broiler chickens.…”
Section: Discussionmentioning
confidence: 93%
“…The oligomers of liquid MHA-FA are poorly absorbed (Saunderson, 1991) and of a lower bioavailability in poultry compared to the commercial product mix of mono-, di-and oligomers (Van Weerden et al, 1992). Maenz and Engele-Schaan (1996b) also reported that in broilers there was conversion of L-MHA into non-absorbable by-products during its passage through the gastro-intestinal tract. Additionally, Malik et al (2006) showed that liquid MHA was, in fact, more slowly absorbed throughout the digestive tract of pigs than L-Met, which agrees with Drew et al (2003) who observed similar results in broiler chickens.…”
Section: Discussionmentioning
confidence: 93%
“…Maenz and Engele-Schaan (1996a) reported a significant conversion of DL-HMBA in non-absorbable subproducts during their passage through the gastrointestinal tract. Furthermore, Lingens and Molnar (1996) have indicated that methionine absorption in broilers was significantly higher when given as DLM compared to HMBA.…”
Section: Resultsmentioning
confidence: 99%
“…All three studies reported that 10% to 20% of the original radiolabelled MHA-FA activity in the feed was present in the distal sections of the SI compared to 3.5% to 5% for methionine, thus in agreement with our results. Moreover, HPLC analysis of gut contents from the distal ileum showed that only 10% of the residual radioactivity was associated with MHA-FA, suggesting that the compound had been metabolized during intestinal transit (Maenz and Engele Schaan, 1996a) and further supporting metabolism by gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in chicken (Esteve Garcia and Austic, 1993;Lingens and Molnar, 1996;Maenz and Engele Schaan, 1996a) used radiolabelled methionine and MHA-FA and estimated intestinal absorption based on residual radioactivity in intestinal contents. This method is not affected by bacterial metabolism of methionine and MHA-FA since the radiotracer would remain within the intestinal contents even following metabolism.…”
Section: Discussionmentioning
confidence: 99%